Repurposing Drugs for the Management of Patients with Confirmed Coronavirus Disease 2019 (COVID-19) - Lovato, Evellyn C. W.; Barboza, Lorena N.; Wietzikoski, Samantha; de Souza, Amanda Nascimento Vasques; Auth, Pablo Alvarez; Junior, Arquimedes Gasparotto; dos Reis Lívero, Francislaine Aparecida (Current Pharmaceutical Design, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), termed coronavirus disease 2019 (COVID-19) by the World Health Organization, is a newly emerging zoonotic agent that emerged in China in December 2019. No specific treatment for COVID-19 is currently available. Usual palliative treatment includes maintaining hydration and nutrition and controlling fever and cough. The clinical severity and extent of transmission need to be determined, and therapeutic options need to be developed and optimized. Methods: The present review discusses the recent repurposing of drugs for COVID-19 treatment. Results: Several compounds, including remdesivir, lopinavir, ritonavir, interferon-β, ribavirin, chloroquine/ hydroxychloroquine, azithromycin, tocilizumab, and ivermectin, have emerged as promising alternatives. They block the virus from entering host cells, prevent viral replication, and attenuate exacerbation of the host's immune response. Conclusion: Although some evidence indicates the positive actions of different classes of compounds for the treatment of COVID-19, few clinical assays have been established to definitively demonstrate their therapeutic value in humans. Multicenter clinical studies are urgently needed to validate and standardize therapeutic regimens that involve these agents. Although science has not yet presented us with a specific drug against COVID-19, the repurposing of drugs appears to be promising in our fight against this devastating disease.
Keywords: ribavirin